2019
DOI: 10.1002/mgg3.722
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon targeted resequencing for SLC2A9 and SLC22A12 identified novel mutations in hypouricemia subjects

Abstract: Background To identify potential causative mutations in SLC2A9 and SLC22A12 that lead to hypouricemia or hyperuricemia (HUA). Methods Targeted resequencing of whole exon regions of SLC2A9 and SLC22A12 was performed in three cohorts of 31 hypouricemia, 288 HUA and 280 normal controls. Results A total of 84 high‐quality variants were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Analyzing mutations through bioinformatics might help explain the related causes of RHUC ( 13 ). Previous experiments showed that changing one amino acid to p.R90H significantly lowers URAT1’s ability to transport uric acid, but it does not affect how it is produced or where it is located in the cell membrane ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing mutations through bioinformatics might help explain the related causes of RHUC ( 13 ). Previous experiments showed that changing one amino acid to p.R90H significantly lowers URAT1’s ability to transport uric acid, but it does not affect how it is produced or where it is located in the cell membrane ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among Roma populations and in Korea, where the same URAT1 mutant alleles were repeatedly identified, lower frequencies of GLUT9 mutant alleles than of URAT1 mutant alleles were reported [ 24 , 25 , 26 ]. In China, screening of the URAT1 and GLUT9 genes for mutations was performed in 31 individuals with hypouricemia (SUA concentration ≤2.0 mg/dL) selected from the general population [ 27 ], and this showed that the number of people with GLUT9 mutations was lower than that of people with URAT1 mutations (two vs. four, no mutations in the URAT1 or GLUT9 genes were found in the other 25 individuals). In this study, neither the URAT1 W258X nor R90H mutant alleles, which are the predominant genetic causes of renal hypouricemia in Japan and Korea, were identified.…”
Section: Genetic Basis For the Epidemiological Features Of Hypouricemiamentioning
confidence: 99%